Anti‑Corruption Lawsuits Filed by the Prosecutor: Balancing Private and Public Interests - A. A. Dolgiev (Actual Problems of Russian Law, 2026)
The paper examines the problem of applying general statutes of limitations established by civil legislation to anti‑corruption claims filed by prosecutors. The author identifies a substantial contradiction between the civil law principles of legal certainty and stability of commerce, which underlie the institution of limitation of actions, and the public‑law tasks of combating corruption, ensuring the inevitability of liability, and protecting the foundations of the constitutional order. Opposing scientific positions are considered: from a complete denial of the applicability of limitation of actions to such claims to practical criticism of the consequences of its application. The legal position of the Supreme Court of the Russian Federation, which insists on the mandatory application of general time limits due to the principle of equality of participants in civil transactions, is examined. It is demonstrated that established judicial practice highlights a serious legislative gap that does not take into account the public‑law nature of anticorruption lawsuits. The author argues for the necessity of comprehensive legislative reform, proposing the establishment of a special procedural regime featuring differentiated limitation periods that run from the moment the offense is discovered, as well as the reclassification of such cases to the framework of administrative procedure.